﻿The bee genus Anthidiellum in Vietnam: descriptions of five new species and the first male of Anthidiellum coronum (Hymenoptera, Megachilidae) - Ngat Thi Tran; Michael S. Engel; Cuong Quang Nguyen; Duong Dinh Tran; Lien Thi Phuong Nguyen (ZooKeys, 2023)
The Vietnamese fauna of bees in the Anthidiellum Cockerell (Megachilinae, Anthidiini) is reviewed. Seven species are recognized, representing two subgenera. Five new species are described and figured as: Anthidiellum (Clypanthidium) nahang Tran, Engel & Nguyen, sp. nov., A. (Pycnanthidium) ayun Tran, Engel & Nguyen, sp. nov., A. (P.) chumomray Tran, Engel & Nguyen, sp. nov., A. (P.) flavaxilla Tran, Engel & Nguyen, sp. nov., and A. (P.) cornu Tran, Engel & Nguyen, sp. nov. from the northern and central highlands of Vietnam. Two previously described species are newly recorded for the fauna: A. (P.) carinatum (Wu) and A. (P.) coronum (Wu), with the male of the latter species described and illustrated for the first time. An identification key is provided for all species of Anthidiellum occurring in Vietnam.